About development of expert possibilities for consideration of equipment projects and technological decisions - D. J. Lobach (Системный анализ и прикладная информатика)
The purpose of the research described in the article is to formulate and substantiate the methodology for analyzing quantitative patterns of parameters of projects, devices, systems and technologies, that can be used for relative or rating comparison of projected, planned or applied investigated objects without using long-term experimental or operational data.The proposed approach to the analysis of quantitative patterns makes it possible to conduct a primary assessment of the advantages of innovative technologies, acomparative assessment of the safety of technical complexes, a targeted pre-operational assessment of equipment parameters, and to form planned distinctive parameters for the implementation of experimental and commercial technical projects.